A prática do letramento literário na escola Lar de Maria: literatura infantil para alunos em processo de alfabetização - MENDES, Márcia Cristina Tocantins (2017)
With the practice of literary literacy at school Home of Mary: children's literature for students in literacy. We sought to understand the concept of literacy, literacy and children's literature and how the literary literacy practices are being developed and consequently how children's literature is contributing in student literacy. The research has qualitative and used for data collection, questionnaires with students and observation in the classroom. There was a major development with the class in relation to learning. Children who have difficulty with reading have a positive progress due to literary practice. In this sense, this study enabled the perception of the importance of children's literature, the fact that when working early with the kids, they will have the taste for reading.